2019
DOI: 10.1002/ccd.28222
|View full text |Cite
|
Sign up to set email alerts
|

In‐hospital gastrointestinal bleeding following percutaneous coronary intervention

Abstract: ObjectivesThis study aims to examine in‐hospital gastrointestinal (GI) bleeding, its predictors and clinical outcomes, including long‐term outcomes, in a national cohort of patients undergoing percutaneous coronary intervention (PCI) in England and Wales.BackgroundGI bleeding remains associated with significant morbidity, mortality, and socioeconomic burden.MethodsWe examined the temporal changes in in‐hospital GI bleeding in a national cohort of patients undergoing PCI between 2007 and 2014 in England and Wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Stent placement is a significant risk factor for new gastrointestinal bleeding, with a risk between 1.3% and 2.4% for GI bleeding within 30 days of ACS in patients on dual antiplatelet therapy (DAPT) [1,2]. Gastrointestinal bleeding following ACS is associated with increased morbidity and mortality [3][4][5][6][7][8]. Fecal occult blood testing (FOBT) has been used in studies in an attempt to predict the need for DAPT discontinuation and assess the bleeding risk of DAPT [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Stent placement is a significant risk factor for new gastrointestinal bleeding, with a risk between 1.3% and 2.4% for GI bleeding within 30 days of ACS in patients on dual antiplatelet therapy (DAPT) [1,2]. Gastrointestinal bleeding following ACS is associated with increased morbidity and mortality [3][4][5][6][7][8]. Fecal occult blood testing (FOBT) has been used in studies in an attempt to predict the need for DAPT discontinuation and assess the bleeding risk of DAPT [9,10].…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 However, abundant evidence showed that the high incidence of bleeding is mainly concentrated within 1 week of the disease course. 7 Hence, it is important to choose the appropriate medications to prevent GI bleeding. It is recommended that patients with myocardial infarction take proton pump‐inhibitors (PPIs) or H2 receptor antagonists (H2RAs) at the same time as antithrombotic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…But the application of combined antiplatelet therapy also has its disadvantages, which is to increase the incidence of gastrointestinal (GI) complications, such as ulcers and GI bleeding 5,6 . However, abundant evidence showed that the high incidence of bleeding is mainly concentrated within 1 week of the disease course 7 . Hence, it is important to choose the appropriate medications to prevent GI bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…GIB is one of the complications of patients admitted to cardiology, which is common in acute myocardial infarction [1], percutaneous coronary intervention (PCI) [2]and anticoagulant or antiplatelet drugs [3]. Not only the length of stay and hospitalization expenses increased, but also lead to other organ dysfunction or even failure, and may cause death in severe cases.…”
Section: Introductionmentioning
confidence: 99%